Suitability of Growth Media and Carbon Source for EPS Production by Lysinibacillus macroides - Andharia, Kartik; Shilpkar, Prateek; Shah, Mayur; Kundu, Susanta (Asian Journal of Biological and Life Sciences)
Exopolysaccharides (EPS) are carbohydrate polymers excreted by bacteria and fungi in the external environment of their cell walls. This study aims to obtain EPS-producing bacteria from the rhizosphere soil of the legume plant. Isolation and screening of potential organisms were performed using the serial dilution method and YEM agar. Based on the mucoid characteristics, 07 isolates were selected for further EPS production from 12 obtained isolates. These 07 isolates were again inoculated in YEM broth and incubated. After incubation, extraction and purification of EPS were carried out by centrifuging the medium at 10000 rpm. Then the supernatant was recovered and chilled ethanol (3 times the volume) was added. Isolate No. KR7 was found more potential with 4.4 g L-1 EPS production in YEM broth. 16S rRNA sequencing identified it as Lysinibacillus macroides. Different growth media were used to obtain the highest EPS and found Media-6 suitable for that with 16.5 g L-1 EPS production. Bagasse can be a cheaper carbon source with 5.5 g L-1 EPS production.
Keywords: Bagasse; Exopolysaccharide; Growth media; Modified YE medium